Experimental and theoretical studies of a diving wall column used for the separation of high purity products in biodiesel production - Othman, Mohamad R.; Harun, N.; Wan Ibrahim, W. H.; Badhrulhisham, Abdul Aziz (2017)
Typically, fractionation of oleochemical products in Malaysia used conventional distillation columns (CDCs) and none so far imply DWC (dividing wall column) mainly due to the lack of understanding of its design, control and operation. In this research project, a systematic simulation based approach for the design of DWC have been proposed. A four column confguration model were developed to represent DWC internal sections and was succesfully simulated using Aspen Plus. Moreover, sensitivity analysis and optimization work shows that the model were found to be more accurate in representing the behaviour of DWC. Apart from that, our techno-economic and environmental feasibility study shows that compared to CDC, DWC saves up to 6% in capital cost and more than 30% savings for utility cost. In addition to the theoritical study, a DWC pilot plant have been built at Universiti Malaysia Pahang. The pilot plant was design on borosilicate glass components and operated under vacuum condition with temperature up to 200oC. The feed capacity is in the range of 5 - 7 kg/h for different type of oleochemical products. We also proposed a novel AHP-HAZOP for process hazard analysis and implement it to the pilot plant. With the realization of the pilot plant, future exciting work will be explore particularly on the operation and controllability. We believe such study integral work between theoritical and experimental scale is important to gain the operation experience for future industrial implementation.